Caracterização da pecuária familiar na região da Campanha Meridional: estudo de caso no município de Bagé-RS - Porto, Rafael Gastal (2008)
This thesis examines farm family livestock as a productive social framework in agricultural farming, under the numerous and different production, reproduction and manifestation systems, seen in Brazilian agriculture. In this sense, this study wants to show evidences of the existence of this social category in Bagé/RS, Rio Grande do Sul State, Southern Brazil. The objective of this work was to characterize farm family livestock in terms of labour use, land structure, production systems, market access and opportunities, access to governmental resources and services and, finally to portray their social-demographic profile. Direct interviews were conducted with 40 family livestock farms during the months of May and June 2007, in the following rural areas: Palmas (Coxilha das Flores, Pedra Grande, Toca, Catarina and Lixiguana), Olhos D'Água, Coxilha do Haedo, Serrilhada and Santa Tecla, where independent specialized family farms are most representative. Multivariate analysis followed by statistical inference were used to examine the data. The features of these farms are adherent to the theoretical concepts of agricultural farming, as far as their own livestock production system characteristics and adaptability to the environment are concerned. Furthermore, these farm family livestock reveled characteristics of production unit of family base within the livestock sector analysed in this investigation. The results concluded that family livestock farms are of fundamental importance for sustainable agricultural development as far as the re-shaping of rural spaces and raise questions about the models of governmental infrastructure policies that should be put in place to meet this specific rural sector demands.